The Analysis of Compounding In Children Story Book Dumbo The Magical Story By Walt Disney And Its Implications As Teaching Materials For Junior High School Students - Irawati, Risya Ayu; Soemantri, Ypsi Soeria; Wagiati, Wagiati; Kadir, Puspa Mirani (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
The study aims to describe the formation of compounding in children story book Dumbo The Magical Story, written by Walt Disney. This study also aims to reveal types of compounding that is mostly found in the object, and to reveal the reasons. This study also describes the implications of compounding as teaching materials in narrative text for Junior High School Students. This is a qualitative with a descriptive method. The data used in this study were the compound words in children book Dumbo The Magical Story. The data collection technique used was note-taking. To measure the implications level of compounding as teaching materials in narrative text. A survey was done to 10 Junior High School students using Likert scale. The data were analysed by matching method with lexical distribution technique. The study shows than the compounding found in Dumbo The Magical Story has 3 forms namely nominal compounding, verbal compounding, and adjectival compounding. The result shows that there were 48 compounding forms consists of 25 compounding of noun+ noun, and 23 compounding of noun + adjective. it was found 6 compounding of verb+verb, 4 compounding of verb+ adjective, 5 compounding of verb + noun, and 1 verb +adjective. in the adjectival compounding, it was found 2 compounding of adjective+ adjective, 3 compounding of adverb + adjective, and 1 adjective + adverb. The form of noun+noun is mostly found in the study. That was because the target readers of the book are children so that the words used were arranged accordingly to make them understand. The implications of compound words as teaching materials in narrative text shows 3,86 out of 5 scale by using The Likert scale.Key words : compounding,  children story book, teaching material, narrative, JHS students